Macroeconomics - Arnold, Roger A. (South-Western College Pub., 2000)
Packed with intriguing pop culture examples to which you can relate, the text bolsters interest in economics by illustrating unexpected places economics occurs, how economic forces link events around the world to your lives, and how economics can be used as a tool in understanding the world.In addition, the eighth edition is integrated with such powerful resources as 'ThomsonNOW', 'Aplia', and the 'Tomlinson Videos'. These resources allow you to gain a customized learning path tailored to your specific areas of strength and weakness, ensuring you gain complete mastery of course content. With new content reflecting a changing economy and new resources catering to the needs of a changing classroom, "Macroeconomics", 8e is your ideal solution for the principles course.